The global/local (limited to some regions) effect of cesarean delivery on the risk of pediatric allergic rhinitis: a systematic review and meta-analysis - He, Xingyi; Zhang, Shipeng; Wu, Jiamin; Fu, Qinwei; Zhang, Qinxiu; Peng, Wenyu (Frontiers in Pediatrics, 2023)
Background Allergic rhinitis is a chronic and refractory disease that can be affected by a variety of factors. Studies have shown an association between cesarean section and the risk of pediatric allergic rhinitis. Methods The PubMed, Springer, Embase, Cochrane Library, and Web of Science databases were searched to retrieve all studies published from January 2000 to November 2022, focusing on the relationship between cesarean section and the risk of pediatric allergic rhinitis. A meta-analysis was conducted to find a correlation between cesarean section and the risk of pediatric allergic rhinitis. A subgroup analysis was performed, considering the region and family history of allergy, after adjusting for confounding factors. Pooled odds ratios (ORs) were calculated, publication bias was assessed using a funnel plot, and heterogeneity between study-specific relative risks was taken into account. Results The results showed that cesarean section was significantly associated with an increased risk of pediatric allergic rhinitis (OR: 1.27, 95% CI: 1.20–1.35). Subgroup analysis stratified by region indicated that cesarean section increased the risk of pediatric allergic rhinitis, with the highest increase in South America (OR: 1.67, 95% CI: 1.10–2.52) and the lowest in Europe (OR: 1.13, 95% CI: 1.02–1.25). The results of the subgroup analysis stratified by family history of allergy indicate that family history of allergy was not associated with the risk of pediatric allergic rhinitis. Conclusion An association exists between cesarean section as the mode of delivery and the increased risk of pediatric allergic rhinitis, and cesarean section is a risk factor for allergic rhinitis.